Impact of the Clinical Trials Act 2018 on clinical trial activity in Japan from 2018 to 2020: a retrospective database study using new and conventional Japanese registries - Taruno, Hiroyuki; Oba, Mari S; Takizawa, Osamu; Kikuchi, Kayoko; Matsui, Kazuaki; Shikano, Mayumi (BMJ Open, 2022)
ObjectiveTo clarify the impact of Japan’s Clinical Trials Act (CTA), which was enacted in April 2018, on subsequent clinical trial activity through an analysis of Japanese registry data.DesignRetrospective database study.SettingWe extracted information on clinical intervention studies registered between 1 April 2018 and 30 September 2020 in the conventional University Hospital Medical Information Network Clinical Trials Registry (UMIN-CTR) and the new Japan Registry of Clinical Trials (jRCT). We collected and analysed information on registration dates, intervention types, funding, secondary sponsors and use of designated staff in multidisciplinary roles (research planning support, research administration, data management, statistical analysis, monitoring and auditing). The temporal trends in clinical trial activity after CTA enactment were examined.ResultsA total of 577 CTA-compliant specified clinical trials (ie, studies funded by pharmaceutical companies or studies evaluating the efficacy and safety of off-label drugs or devices in humans) were registered in the jRCT. During the same period, 5068 clinical trials were registered in the UMIN-CTR. The number of specific clinical trials increased immediately after the implementation of the CTA and stabilised in late 2019, whereas the number of clinical trials registered in the UMIN-CTR generally declined over time. Specified clinical trials that received industry funding and public grants were more likely to use designated staff in multidisciplinary roles.ConclusionsThe implementation of the CTA has not reduced the number of specified clinical trials, but has reduced the total number of intervention trials. The use of designated staff in multidisciplinary roles is associated with funding, secondary sponsors and multicentre studies. It was inferred that funding was needed to establish research infrastructure systems that support high-quality research.